DEATH AS THE “REAL”: A PSYCHOANALYTIC READING OF MATTHEW ARNOLD’S YOUTH AND CALM - Alexei Wahyudiputra (POETIKA, 2021)
Matthew Arnold was one of the poets who paid special attention to youth and the dynamics of youth culture in the Victorian era. Living in an era that stimulated modern times, Arnold produced writings that can be classified as historical records, although not factual, of society's reactions to the fundamental social and cultural changes of the time. The literary arena was particularly affected, as the Victorian era marked the beginning for poets and artists alike to shed the romantic spirit that they had breathed into their works and adapt to the technological and industrial realities around them. This article explores Matthew Arnold's poem entitled “Youth and Calm”. The poem explores a stream of consciousness that contemplates “the youth" and their dreams. This study aims to uncover the meaning of the poem based on its textual composition without correlating it with Arnold's other works. Using theoretical phenomenology tools to dissect language phenomena and the Freudo-Lacanian method in interpreting the theme, this study led to the revelation that the poem talks of “death” as a symbolically repressed object. Matthew Arnold merupakan salah satu penulis puisi yang menaruh atensi lebih pada pemuda dan juga dinamika kebudayaan muda-mudi pada era Victoria. Hidup di dalam yang era mendasari kultur modern, Arnold menghasilkan karya-karya yang dapat diklasifikasikan sebagai catatan historis, meskipun tidak faktual secara absolut, terkait reaksi masyarakat dalam menghadapi perubahan sosial dan kultural yang begitu mendasar di kala itu. Terlebih dalam arena literatur, kehadiran era Victorian merupakan awal penanda bagi penyair dan produser seni lainnya untuk mulai menanggalkan jiwa romantisme yang mereka hembuskan pada tiap karya dan beralih pada realita teknologi dan industri di sekitar mereka. Dalam artikel ini, puisi Matthew Arnold yang ditelaah secara mendalam berjudul “Youth and Calm”. Puisi tersebut mengeksplorasi arus pemikiran yang berisikan kontemplasi terhadap figur “pemuda” dan apa yang mereka impikan. Penulisan ini bertujuan untuk menggali makna puisi berdasarkan komposisi tekstualnya dan tanpa menghubungkannya dengan karya Arnold lainnya.  Menggunakan paradigma fenomenologi untuk membedah struktur kebahasaan serta Freudo-Lacanian dalam menginterpretasi tema menghasilkan sebuah makna bahwa “Death” atau kematian merupakan objek yang secara simbolis dipendam oleh subjek youth yang dibahas pada puisi ini.